Did amakudari undermine the effectiveness of regulator monitoring in Japan? - Horiuchi, Akiyoshi; Shimizu, Katsutoshi (Journal of Banking & Finance, 2001)
The principal–agent problem between the regulator, regulated banks, and taxpayers is critical to the viability of the financial system’s safety net. There exists the danger that the regulator will collude with regulated banks to pursue their benefits at the expense of taxpayers, thereby reducing effectiveness of financial supervision. This paper proposes that the human relationship prevailing between the regulatory authorities and private banks referred to as “amakudari” is a form of collusion between the regulator and banks that endangers the safety net mechanism in Japan. Statistical analysis of data on regional banks shows that those banks accepting post-retirement officials from the Ministry of Finance have reduced capital adequacy levels and increased non-performing loans. Thus, the statistical result supports the hypothesis proposed in this paper.